The Quality of E-Learning Based on Learning Media Using Moodle LMS on Text of Observation Reports of Grade 10th Students of Vocational School Telkom Shandy Putra Medan - Sukma Adelina Ray; Abdurahman Adisaputera; Isda Pramuniati (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The aims of this study to find out the quality of E-learning based on learning media using Moodle LMS on text of observation. This type of research is development research in the field of education known as Research and Development (R&D). Development research (development research) is research that is used to produce certain products and test the effectiveness of these products (Tegeh and I.M, 2013). The result of this study show that The quality of e-learning based learning media using LMS Moodle which was developed as a learning media on the observation report text material is stated to be a useful and effective contribution in improving the quality of learning outcomes of 10th grade TJA1 Vocational School Telkom Shandy Putra Medan. This is because there is a significant difference in the learning outcomes of the average value of students before using e-learning based learning media (pre-test) ie 57.0 or only about 52% are able to exceed KKM and after using e-based learning media learning using LMS Moodle (post-test) the average value of students increased to 77.0% or can be interpreted as 100% of students able to exceed the KKM. Based on these data the difference is increased by 20% or can be interpreted student learning outcomes increased by 58%.